Miners in front of the Keewalik Hotel before leaving for the Kobuk River, Nome, Alaska, September 29, 1903 - Nowell, Frank H., 1864-1950
Caption on image: Miners who left for Kobuk River on Str. John Reilly. Sept 29th'03. Nowell - 114. PH Coll 413. Album 10.28